The Relationship between Nutrition Knowledge Level and Diet with the Incidence of Chronic Energy Deficiency (CED) in Adolescent Girls at MTsN 3 Surabaya - Herlina Dwi Agustina; Luthfi Rusyadi; Nuning Marina Pengge; Dian Shofiya (Politeknik Kesehatan Kemenkes Surabaya, 2025)
Chronic Energy Deficiency (CED) in adolescent girls is characterized by long-term low energy intake that impacts growth and reproductive health. This study aims to analyze the relationship between the level of nutritional knowledge and diet and the incidence of CED in adolescent girls in MTsN 3 Surabaya. The design of this study is an observational analysis with a cross-sectional approach involving 60 respondents, selected using proportional random sampling techniques. Data were collected through nutritional knowledge questionnaires, diet recall, and Upper Arm Circumference measurements. The results showed that most of the respondents had a level of nutritional knowledge in the category of adequate (61.7%) and poor diet (83.3%). As many as 46.7% of respondents experienced CED. The Chi-Square test showed a significant relationship between the level of nutritional knowledge and the incidence of CED (p = 0.003), as well as between diet and the incidence of CED (p = 0.001). It can be concluded that the level of nutritional knowledge and diet has a significant effect on the incidence of CED in adolescent girls. Therefore, educational efforts and improvement of consumption patterns are needed to prevent CED from adolescence.